2013
DOI: 10.1177/0892705713486132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sample width and inclined angle on flame spread across expanded polystyrene surface in plateau and plain environments

Abstract: To study the effect of sample width and inclined angle on flame spread across expanded polystyrene (EPS) surface, a series of laboratory-scale experiments were conducted in the Lhasa plateau and the Hefei plain. Surface flame height, flame spread rate and preheating zone length were obtained. The dimensionless surface flame height varied as the Àn power of the sample width and 0.7 < n < 0.9. As angle of incline increased, the surface flame height first rose and then dropped. The surface flame height difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…The steady spread means steady heat transfer and basically unchanged preheating length. In addition, the preheating length for downward flame spread in this work is much shorter than that of upward flame spread . This is attributed to the less heat transfer of downward flame spread.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…The steady spread means steady heat transfer and basically unchanged preheating length. In addition, the preheating length for downward flame spread in this work is much shorter than that of upward flame spread . This is attributed to the less heat transfer of downward flame spread.…”
Section: Resultsmentioning
confidence: 74%
“…In addition, the preheating length for downward flame spread in this work is much shorter than that of upward flame spread. 38 This is attributed to the less heat transfer of downward flame spread. As the flame adheres to the façade during downward flame spread, the radiant heat flux of the flame is smaller due to the smaller radiant view factor.…”
Section: Thermal Characteristicsmentioning
confidence: 99%
“…What is more, to analyze the variation of flame size, flame height is quantified. Because of the fluctuating characteristic of flame, flame height is defined as the perpendicular distance from the rear surface of sample to flame tip, where 50% of the flame tip appears …”
Section: Resultsmentioning
confidence: 97%
“…To clear out the variations of flame characteristics of PMMA and PE cylinders during the horizontal flame spread process in elevated pressures, the flame appearance and flame height are analyzed.In this study, the change of flame appearance is reflected in the aspects of flame structure, color, and molten characteristic. What is more, to analyze the variation of flame size, flame height is quantified.Because of the fluctuating characteristic of flame, flame height is defined as the perpendicular distance from the rear surface of sample to flame tip, where 50% of the flame tip appears 14.…”
mentioning
confidence: 99%
“…Previous studies have shown that reduced pressure can lead to completely different fire dynamics and changes in combustion characteristics such as burning rate, flame spreading, physical morphology of the flame and flame temperature. 23 Therefore, we hypothesized that the burning mechanism of PUR at high altitudes could best be understood using a pool fire combustion model taking into account effects of pressure variations.…”
Section: Introductionmentioning
confidence: 99%